Антропологічний матеріал з могильника черняхівської культури Лісові Гринівці - Рудич, Т.О. (Археологія, 2014)
Охарактеризовано антропологічний матеріал з могильника черняхівської культури Лісові Гринівці на Хмельниччині та подано результати зіставлення його із синхронними пам’ятками. Подан антропологический материал из могильника черняховской культуры Лисови Грынивци, расположенного возле г. Хмельницкий. Он представлен 21 погребением, в которых выявлены останки 23 умерших обоих полов разного возраста.
По результатам межгруппового анализа серия мужских черепов из Лисовых Грынивцев демонстрирует наи большую морфологическую и статистическую близость с людьми из могильников масломенчской группы вель барской культуры Польши. В населении вельбарской культуры часто видят, прежде всего, германцев. Однако надо отметить, что основной антропологический массив германских популяций vi—Xiii вв. сформировался на иной антропологической основе, является довольно однородным и морфологически и статистически существен но отличается от населения вельбарской культуры Польши. женская часть популяции из Лисовых Грынивцев демонстрирует большую морфологическую и статистическую близость с сериями черняховской культуры Мол довы и частично Северного Причерноморья (ранжевое, Коблево). Скелеты из погребений с западной и северной ориентацией на могильнике Лисови Грынивци морфологически не различаются. Presented is the anthropological material from lisovi hrynivtsi, a Chernyakhivska culture burial ground situated near khmelnytskyi. it includes 21 burials where the remains of 23 dead of both sexes and various ages were found.
according to the results of intragroup analysis, a series of male sculls from lisovi hrynivtsi demonstrates the nearest morphologic and statistical closeness with the people from burial grounds of Maslomenska group, velbarska culture in Poland. the Germans are the most often seen in the population of velbarska culture. however, it should be noted that the main anthropological mass of the German population of the period from the 6th c. to the 13th c. was formed at the other anthropological base, that it is quite homogeneous, and significantly differs morphologically and statistically from the velbarska culture bearers in Poland. Female part of population from lisovi hrynivtsi demonstrates the morphological and statistical closeness to the groups of Chernyakhivska culture in Moldova and partially in the north coast of the Black sea (ranzheve, kobleve). the people from the graves oriented to the west and those oriented to the north at the lisovi hrynivtsi burial ground are not morphologically different.